Analisis Rantai Pasok Input Usaha Keramba Jaring Apung di Kelurahan Haranggaol Kecamatan Haranggaol Horison Kabupaten Simalungun Provinsi Sumatera Utara - Donda Tamauli Matondang; Hendrik; Tince Sofyani (Jurusan Sosial Ekonomi Perikanan, 2021)
The use of input in supporting the success of fish cultivation is the availability of seeds and feed that qualify both quality, quantity and continuity. The input supply chain system in floating net keramba business is known through chain and flow chain actors. The goal that wants to be achieved in this study is to find out the amount of use of seed input and feed and input supply chain system in Haranggaol Village.Research was carried out in Haranggaol Village of Simalungun Regency of North Sumatra Province on February 9 – March 9, 2020. This research is a descriptive study with survey methods. The results showed that KJA Business in Haranggaol Village with a total of 7,075 bags per year requires tilapia fish seed (Monoculture) of 95,139,000 tails, Goldfish and Tilapia (Polyculture) seeds are tilapia seeds 1,520,000 tails and goldfish 289,000 tails and catfish seeds are 138,000 tails. The amount of feed for tilapia is 36,266,180 kg, goldfish and tilapia feed is 17,431,160 kg and catfish feed is 12,582 kg. The mechanism of seed input supply chain involves Seeding Cultivation and Enlargement Cultivation while feed supply chain involves Feed Factory, Large Trader and Enlargement Cultivation. There are product flows, financial flows and information flows in Haranggaol Village.